Prenatal diagnosis of alpha-thalassemia-1 (SEA type) by chorionic villus sampling - Chanprapaph P. (2014)
To describe the experience of prenatal diagnosis for Hb Bart's disease, by chorionic villus sampling (CVS) with DNA analysis.